Integrated Methodology for the Planning of Electrical Distribution System Considering the Continuity of the Service and the Reduction of Technical Losses (2019)
This article presents a methodology that allows to obtain an optimal plan of re-configuration of the local distribution system to 13.2 kV, considering the improvement in the continuity of the service to the users and the reduction of technical losses in the network. The methodology consists of two phases: The first deals with the problem of the reconfiguration of primary distribution circuits through permanent measures and temporary measures. The second phase ad-dresses one of the main problems in the planning of the expansion of distribution networks, which consists of the location of the distribution substations, which represent the main link between transmission and distribution systems. The implementation of the methodology allows to simulate different scenarios and constitutes a tool for the planning of the distribution system of the regional operators (OR) of the local distribution systems (LDS). © 2019, Springer Nature Switzerland AG.